Kajian Fenimisme Dalam Hubungan Internasional Kontemporer Studi Kasus : Peranan Beauty Vlogger Dalam Perdagangan Kosmetik Internasional - Chalimatus Sa’diyah; Ismiyatun Ismiyatun (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2021)
The researcher aims to describe the supply, potential, development, tourism diplomacy in Dieng Tourism Destinations. this Skripsi writing the author uses the basic framework of Tourism Diplomacy theory to achieve the interests tourism activities supported by various facilities and services. And the research method used through data collection techniques by means of interviews, documentation, internet and surveys with qualitative descriptive types. The collected data is then analyzed and grouped based on existing research problems. The results of the study show that Tourism Diplomacy in making Dieng International Tourism Destinations, consists of Diplomacy by Stakeholders and Diplomacy through Eent. Diplomacy by stakeholders includes: Stakeholders that have a direct influence on tourism activities, stakeholders who become community motivators, stakeholders in service providers and marketing and stakeholders who have an indirect influence on tourism activities. And diplomacy through events such as: DCF, Central Java Wow, Merdada Festiva